2018
DOI: 10.1051/itmconf/20181701016
|View full text |Cite
|
Sign up to set email alerts
|

An Adaptive Contention Window Scheme for 802.11ah WLANs

Abstract: Abstract. In order to cope with the rapid development of the Internet of things, IEEE working group has proposed a new wireless network technology, 802.11ah. IEEE 802.11ah operates at sub 1GHz band, and can provide long transmission range, wide coverage, while supporting more than 6,000 of station to be connected. In order to alleviate the high collision probability, 802.11ah MAC protocol involves in the RAW (restricted access window) mechanism combined with grouping mechanism. However, in 802.11ah WLAN (wirel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…However, most STAs operate in sleep mode in IEEE 802.11ah WLAN, and it is projected that the network would have a considerably greater collision probability at the beginning of a BI than at the end. To mitigate these limitations, the authors in [ 130 ] proposed an adaptive contention window technique in which the contention window size is optimized at the beginning of the BI and subsequently decreased after the transmission is successfully completed. Through simulations, it was demonstrated that the suggested method might improve IEEE 802.11ah WLAN performance.…”
Section: Mac Features Of the Ieee 80211ah And Current Resource Alloca...mentioning
confidence: 99%
“…However, most STAs operate in sleep mode in IEEE 802.11ah WLAN, and it is projected that the network would have a considerably greater collision probability at the beginning of a BI than at the end. To mitigate these limitations, the authors in [ 130 ] proposed an adaptive contention window technique in which the contention window size is optimized at the beginning of the BI and subsequently decreased after the transmission is successfully completed. Through simulations, it was demonstrated that the suggested method might improve IEEE 802.11ah WLAN performance.…”
Section: Mac Features Of the Ieee 80211ah And Current Resource Alloca...mentioning
confidence: 99%
“…This section presents some recent works that mitigated the drawbacks of the BEB algorithm in IEEE 802.11 standards, including IEEE 802.11ah [28][29][30][31][32][33][34][35][36]. As mentioned earlier, the IEEE 802.11ah MAC protocol of RAW reduces collisions in highly congested network scenarios by using EDCA and DCF access schemes to manage transmission attempts.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, this kind of threat needs to be mitigated. The authors in [32] proposed a combination mechanism of RAW and adaptive scheme used to calculate an optimal value of the CW size at the beginning of the beacon interval, then slowly halving it when the transmission is successful. The performance of the proposed scheme has been evaluated using the OPNET simulator.…”
Section: Related Workmentioning
confidence: 99%
“…One of the essential approaches is to modify the contention window size to maximize the network performance. The optimal contention window was used in prior studies, but once the window size was set, it did not alter 21 . The communication problems between nodes can be mitigated when the contention window is wide, which reduces the latency.…”
Section: Introductionmentioning
confidence: 99%
“…The optimal contention window was used in prior studies, but once the window size was set, it did not alter. 21 The communication problems between nodes can be mitigated when the contention window is wide, which reduces the latency. At the same time, it will use less energy because there will be less data retransmission, but it will need more ability to keep a large contention window.…”
mentioning
confidence: 99%